Bimbingan teknis pembuatan bokashi berbasis komba-komba sebagai campuran media tanam budidaya sayuran untuk mewujudkan urban farming: Technical Guidance on bokashi production based on komba-komba as a mixed planting medium for vegetable cultivation to realize urban farming - Andi Nurmas; Robiatul Adawiyah; Makmur Jaya Arma; Norma Arif; Sarawa Sarawa; Dirvamena Boer (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
Urban expansion has led to a significant decline in agricultural land and green open spaces. Urban farming emerges as an alternative approach by optimizing and managing limited open areas among urban structures. Urban farming initiatives conducted by the Flamboyan Dasawisma Group in Padaleu Village, Kambu District, Kendari City, provide green vegetables as a nutritional source, enhance environmental quality, and support efforts to mitigate the impacts of global warming. This Community Service Program (PKM) aims to improve community knowledge and skills while increasing awareness of the importance of utilizing household yard spaces to achieve family food security and environmental sustainability through urban farming practices. The program was implemented through educational outreach to community groups about the benefits and application of urban farming, followed by hands-on mentoring in establishing an urban farming garden as a demonstration model for the Padaleu Village community. The findings reveal a positive response from members of the Flamboyan Dasawisma Group, along with strong expectations for the program's continued support. This community service initiative is anticipated to provide tangible benefits to the local community, particularly the Flamboyan Dasawisma Group, by reducing household expenditures. Furthermore, community members demonstrated high enthusiasm for cultivating vegetables using the urban farming system.